PROFESIONALISME GURU DALAM MENYAMPAIKAN MATERI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Rusiadi Rusiadi (JIP: Jurnal Ilmu Pendidikan, 2023)
The role of the teacher is not only as a teacher (teaching), but the teacher must act as a trainer (coach), a professional teacher who acts like a sports coach. He helps his students more in games, the difference between the games is learning (game of learning) as a trainer, the teacher encourages his students to master learning tools, motivates students to work hard and achieve the highest achievements. Then the counselor, the teacher will become a friend of the students, a role model in person who invites respect and familiarity from students, creates an atmosphere where students study in small groups under the guidance of the teacher. Then the learning manager, the teacher will act like a company manager, he guides his students to learn, takes the initiative, brings out the best ideas he has. Mastery of methodology is also necessary to provide knowledge, skills and values related to the subject. Mastery of evaluation techniques is also absolutely necessary for a teacher, with mastery of evaluation techniques the teacher can properly assess the process and results of teaching and learning.